1992
DOI: 10.1136/jnnp.55.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Stroke topography and outcome in relation to hyperglycaemia and diabetes.

Abstract: In a prospective study to analyse stroke topography and outcome in diabetics and to determine the prognostic value ofblood glucose and glycosylated haemoglobin estimation, we evaluated 176 patients with acute stroke. The patients were classified into four groups on the basis of history, fasting glucose, and glycosylated haemoglobin: euglycaemic patients with no history of diabetes, stress hyperglycaemia, newly diagnosed diabetics, and known diabetics. A high prevalence of undiagnosed diabetes was shown. No dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
128
2
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(153 citation statements)
references
References 39 publications
15
128
2
6
Order By: Relevance
“…A lower frequency of hemorrhagic stroke recorded in this study was in agreement with a lower frequency of intracerebral hemorrhages in diabetic patients observed by Lithner et al 33 and by Kiers et al 34 Unlike for chronic hypertension and hemorrhagic stroke, most case control studies examining the relationship between DM and hemorrhagic stroke have not concluded that DM is an independent risk factor for both intracerebral and subarachnoid hemorrhagic stroke.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…A lower frequency of hemorrhagic stroke recorded in this study was in agreement with a lower frequency of intracerebral hemorrhages in diabetic patients observed by Lithner et al 33 and by Kiers et al 34 Unlike for chronic hypertension and hemorrhagic stroke, most case control studies examining the relationship between DM and hemorrhagic stroke have not concluded that DM is an independent risk factor for both intracerebral and subarachnoid hemorrhagic stroke.…”
supporting
confidence: 79%
“…This finding is consistent with Copenhagen stroke studies which showed that there was no relation between admission blood glucose levels and mortality. 19 A similar finding has also been reported from studies conducted elsewhere, 34,40 however, very few studies demonstrated an increased mean glucose level and mortality in diabetic patients. 33 Nonetheless, in non-diabetic patients with stroke, several [41][42] but few have found an increased mortality in hyperglycemic non-diabetic patients compared with euglycemic non-diabetic patients.…”
supporting
confidence: 73%
“…Several aspects of physiology, notably blood pressure, body temperature, blood oxygen saturation, and blood glucose, may be altered after an ischaemic stroke or an intracerebral hemorrhage. Patients with acute ischaemic stroke frequently test positive for hyperglycaemia, which is associated with a poor clinical outcome [2][3][4]. Most studies showed the deleterious effect of early hyperglycaemia, especially in patients with nonlacunar focal or global ischaemia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Increased mortality was evident in the hyperglycemic and diabetic groups (104). Hyperglycemia is associated with lactic acidosis and conversion of penumbral tissue to an infarction, greater final infarct size, and worse functional outcome (104).…”
Section: Glucosementioning
confidence: 99%